SILEK KUMANGO: KEBERADAAN, PEWARISAN, DAN KEARIFAN LOKAL MINANGKABAU - Isral Saputra (Jurnal Elektronik WACANA ETNIK, 2011)
Nowadays, the Minangkabau silek is waning interest and users. Technological developments are considered to be the cause. This article describes the research result of the presence of silek Kumango in Kanagarian Rao-Rao Tanah Datar, West Sumatra. Using ethnographic methods and approaches, it’s also obtained the inheritance and local genius in this silek. There are some functions and symbols that show local content in silek Kumango which are manifested in the succession process, control, and motion itself in this silek.